ALGUNOS ASPECTOS RADIOLOGICOS DE LA SILICOSIS - ROLDAN, UBALDO V (Instituto Politécnico Nacional, Escuela Nacional Ciencias Biología, Laboratorio Zoología, CD MEXICO, DF, MEX, 1949)
The pathology of 300 cases of brucellosis is grouped into the following types of lesions: inflammatory, hyperplastic, vascular, degenerative and pigmentary The inflammatory lesions included skin abscesses, abscesses in the periosteum of the mastoid apoph
REV MEX TUBERCULOSIS
Keywords: ASPECTOS, RADIOLOGICOS, SILICOSIS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; RADIOLOGIA